2018
DOI: 10.1016/j.jiec.2017.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Volatile organic compounds absorption in packed column: theoretical assessment of water, DEHA and PDMS 50 as absorbents

Abstract: A fixed volume packed column was simulated for the absorption at counter-current of four more or less hydrophobic volatile organic compounds (VOCs) in water and in two heavy organic solvents (PDMS 50, a silicone oil) and DEHA (Bis(2-ethylhexyl) adipate)). Reliable values of the mass-transfer coefficients were deduced allowing to calculate the VOCs removal efficiency. Disappointing performances in heavy solvents, lower than 60% for isopropanol and acetone, were computed in a 3 m height column and using mild con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 46 publications
(84 reference statements)
5
26
0
Order By: Relevance
“…Such a result is consistent with data usually reported in the literature and with the sensitivity analysis reported by Hernandez et al [22]. Additionally, Figure 4 highlights that K L a also depends on H VOC,mix which is in agreement with data reported in the literature [12,21,26]. Such an expected result is consistent with the mathematical expression of K L a given by Equation (9).…”
Section: Data From Tatin Et Alsupporting
confidence: 92%
See 1 more Smart Citation
“…Such a result is consistent with data usually reported in the literature and with the sensitivity analysis reported by Hernandez et al [22]. Additionally, Figure 4 highlights that K L a also depends on H VOC,mix which is in agreement with data reported in the literature [12,21,26]. Such an expected result is consistent with the mathematical expression of K L a given by Equation (9).…”
Section: Data From Tatin Et Alsupporting
confidence: 92%
“…A 2.7-fold increase is calculated for the 5-50 • C range. This finding is consistent with results deduced from the literature [11,21] indicating the influence of the Henry coefficient on K L a. Lastly, the influence of the silicone oil volume fraction in the mixture on toluene removal was studied. Authors reported that results were not significant: when the silicone oil volume fraction was doubled (from φ NAP = 10% to φ NAP = 20%), efficiency was improved by only 3%.…”
Section: Data From Tatin Et Alsupporting
confidence: 91%
“…In agreement with the results published earlier considering DEHA and PDMS 50 [44], the interfacial areas simulated using the B-S theory were particularly large (≈ 340 m 2 m -3 ) and 244% higher than the packing specific surface (A p = 139 m 2 m -3 ) which seems unlikely. Such a high discrepancy is not surprising since this correlation was essentially developed with water-like systems with kinematic viscosities in the range 0.14-1.66 m 2 s -1 , which is far to include heavy solvents [52,53].…”
Section: Simulation Of the Hydrodynamicssupporting
confidence: 90%
“…The interfacial area found using the S-S-R theory was compared to the values deduced from the Piché et al and Onda correlations, which were both developed with water-like systems [44,57,58].…”
Section: Simulation Of the Hydrodynamicsmentioning
confidence: 99%
See 1 more Smart Citation